Integrated PBLRQA Teaching E-Module to Improve Critical Thinking and Metacognitive Skills - Ni Gusti Ketut Masmirayani; Sutrisnawati; Mursito S. Bialangi; Abd. Hakim Laenggeng; Lestari M.P. Alibasyah (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
The use of technology in learning remains suboptimal, which affects students' low levels of critical thinking and metacognitive skills. This study aims to develop an integrated e-learning module, PBLRQA, to improve critical thinking and metacognitive skills. The method used is research and development, with the Research and Development (R&D) model and a 4D development model: defining, designing, developing, and disseminating. The research subjects were 30 grade X students, and the research instruments included validation sheets, essay questions to measure critical thinking skills, and observation sheets to assess metacognitive skills. The analysis technique used quantitative and qualitative analysis. The validation results showed a feasibility level of 82.73 percent for the E-Module, in the very good category. The effectiveness test showed a significant increase, with a score of 0.81 for critical thinking skills and 0.85 for metacognitive skills, both in the high category. The conclusion of this study shows that the integrated e-module PBLRQA can significantly improve students' critical thinking and metacognitive skills. This research implies that it effectively improves students' critical thinking and metacognitive skills and supports more interactive, relevant biology learning in the digital era.